Phenomenon of aggressiveness in psychology, psychiatry and social life - Reshetnikov, Mikhail (Advances in Social Sciences Research Journal, 2019)
In this paper, psychological theories and hypotheses explaining possible mechanisms of aggressive behaviour, as well as social and psychological factors facilitating it, are reviewed. Connections between aggressive drive and individual’s motivation, aspirations and psychopathological complexes, as well as influence of contemporary societal crises, are analysed. Manifestations of aggressive symbolism in contemporary arts, theatre and mass media are outlined.